(untitled) (Physical Education, Health and Social Sciences, 2025)
A subset of artificial intelligence (AI), deep learning (DL) is rapidly transforming cancer detection. This review explores how artificial intelligence can enhance digital pathology’s repeatability, workflow efficiency, and diagnostic accuracy by means of data integration from several studies evaluating AI systems for different tumors types. Designed to find melanoma, prostate cancer, and breast cancer metastases, artificial intelligence (AI) tools outperform human experts either exactly or slightly. Moreover, systematic reviews and reproducibility models in existence call for the imperative necessity of standardized assessment and judicious integration into clinical protocols. Despite the breakthroughs achieved, numerous issues with regard to clinical interpretability, generalizability, and ethical utilization persist and remain of major concern. Besides advancing accuracy in medical evaluations, the deployment of artificial intelligence in cancer diagnosis also has the potential to diminish healthcare disparities considerably, particularly in underdeveloped or under-resourced areas. As artificial intelligence platforms evolve and enhance themselves, the prospect of them playing a positive role in patient outcomes and healthcare processes becomes more evident and realized. It should be noted, however, that oncology artificial intelligence technologies are still in their infancy stage of evolution; thus, their safe and effective use in clinical environments is contingent on rigorous validation processes and judicious consideration of ethical implications. The aim of this paper is to examine the evolving role of artificial intelligence in oncologic diagnostics, as well as in-depth analysis of its current strengths and weaknesses, benefits, and strategic long-term guidance that is necessary to facilitate stable, scalable, and equitable clinical adoption.